Towards developing a risk charter for software development projects / Noor Habibah Arshad - Arshad, Noor Habibah (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2001)
The challenge of software development lies in its attempt to satisfy the users' requirements; control and cost management; product's schedule and product's quality. To ensure that these criteria are met, product success and product management success need to be emphasized. Product success deals with goal and purpose while the project management success deals with the project input and output. Project success may be achieved by having an integrated project management process where an important aspect of the process is risk management. The risk management process must be integrated into the plan to enable a project manager to effectively manage the software development. In the software risk management process, risk identification is one of the most important components that needs to be tackled before developing any meaningful risk management strategies. Therefore, in this paper, risks related to software development are identified and discussed.